Can You Consciously Plan your Life? The Course of Human Life According to Charlotte Bühler - Wenderlich, Maja (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2020)
The article is about an outstanding monograph entitled The course of human life by Charlotte Bühler. The author proposes a holistic view of human development, which makes this work timeless. She recognizes three aspects in the course of human life. The first one is the aspect of objective behavior and data - biological processes determining the development and destruction of the human body and its functions. The second is the aspect of experience and subjective data - a set of individual behaviors and experiences possible to determine on the basis of biographical data and established personal experiences. The third one is the aspect of the work or result - personal products of individual life, reflected in the ability to influence other people, the acquired social or historical role. The author also talks about accumulations in life - e.g. periods of outstanding creativity and she notes that human lives differ in this respect. The various aspects behind the main theme of Bühler’s work, which is “devoting one’s life” to something or someone, are discussed.